Key message 4: eat adequate amount of rice, other cereal products (preferably whole grains) and tubers - Mamat, Nik Mazlan; Mat Jusoh, Hanapi; Rajikan, Roslee (National Coordinating Committee on Food and Nutrition, Nutrition Division, Ministry of Health Malaysia, 2010)
It is now widely accepted that the major causes of morbidity and mortality in Malaysia are related to unhealthy eating habits and a sedentary lifestyle. Besides an alarming increase in prevalence of overweight and obesity, diet-related diseases such as type 2 diabetes, cardiovascular disease, hypertension and certain forms of cancer have recorded an increase during the last few decades in Malaysia. The role nutrition plays in addressing these problems have been recognised by the Government with the establishment of the National Nutrition Policy (NP) in 2005 and in line with the NNP, the National Plan of Action for Nutrition of Malaysia (2006-2015) was developed with a broad objective to achieve and maintain the nutritional well being of Malaysians. In order to meet the objective to improve food intake and dietary practices of Malaysians, one of the recommended strategies is to ensure that every individual gets access to information on nutrition. The Malaysian Dietary Guidelines (2010) is a compilation of the latest science-based nutrition and physical activity recommendations prepared by the Technical Working Group on Nutritional Guidelines under the auspices of the National Coordinating Committee on Food and Nutrition (NCCFN). Its aim is To provide advice on how to promote healthy eating and also practise an active lifestyle. Consumer-friendly brochures and pamphlets will be produced to help the general public in understanding the scientific language of the Dietary Guidelines and to help them make informed choices on what constitute a healthy diet. The Malaysian Dietary Guidelines (2010) differ in scope compared to the previous version first published in 1999. The updated guidelines contain 14 key messages as compared to 8 key messages described in the previous guidelines and also contained detailed background paper on each of the key messages. Due to the nature of the dietary guidelines, the background papers were developed as a result of a process of comprehensive, rather than systematic, review of the literature. This publication has included 55 key recommendations under the 14 key messages with some additional recommendations for special population groups. Since food can provide most if not all of our nutrient needs, the basic assumption of the Dietary Guidelines is that nutrient needs should be met primarily through food consumption. It is envisaged that if implemented as a whole, the dietary guidelines should encourage Malaysians to consume less calories, be more active and make wiser food choices.